Changes of the Lithuanian Periodical Structure (1988-1995) - Burneikienė, Genovaitė (Knygotyra, 2024)
The article gives survey of the genesis of the Lithuanian periodicals and analyses the process of press development (in 1988 through 1995). The article deals with the conditions that determined emergence of the uncensored press of Sąjūdis movement during the Resurgence period (in 1988). The article reveals impact of publications of Sąjūdis movement on the Lithuanian society and the official press (in 1988 appeared about 70 publications of Sąjūdis movement) and the ways used by local individual editorial offices to disengage from "care" of the periodical press of the Communist Party. The article investigates development of the system of the Lithuanian periodical press after adoption of the Law on Mass Media (February 09, 1990) that liberated editorial offices from dependence on the Party and established the main provisions of freedom of the press. Communication process after 1990 resulted in appearance of new types of periodicals, in change of the status, publication structure and orientation of previous periodicals: a new system based on principles of self-adjustment was emerging. Appearance of multitude of different publications caused a problem of classification as there were neither criteria of classification nor types of groups of the periodicals identified. Therefore, certain data provided by statistical publications on the press do not reveal reality of journalistic practice. The author investigates structural development of the groups of different types of publications, gives survey of classification models provided by investigators of journalism and provides criteria for classification of periodicals that will enable to better reveal structural changes taking place in the system of the Lithuanian periodicals and development trends of the periodical press.